2013
DOI: 10.1371/journal.pone.0079414
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Lymphocytic Neurotrophins Profiles in Systemic Lupus Erythematosus: a Case-Control Study

Abstract: BackgroundNeurotrophins play a central role in the development and maintenance of the nervous system. However, neurotrophins can also modulate B and T cell proliferation and activation, especially via autocrine loops. We hypothesized that both serum and lymphocytic neurotrophin levels may be deregulated in systemic Lupus erythematosus (SLE) and may reflect clinical symptoms of the disease.MethodsNeurotrophins in the serum (ELISA tests) and lymphocytes (flow cytometry) were measured in 26 SLE patients and 26 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…16 Similarly, few reports are available regarding peripheral BDNF levels in SLE and data are conflicting. [32][33][34] BDNF is the most abundant neurotrophin in brain tissue and has been implicated in several neurological and psychiatric disorders. 35 It is difficult to interpret the discrepant data that have suggested both increases and decreases in peripheral BDNF in SLE patients and the association or not with NP manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…16 Similarly, few reports are available regarding peripheral BDNF levels in SLE and data are conflicting. [32][33][34] BDNF is the most abundant neurotrophin in brain tissue and has been implicated in several neurological and psychiatric disorders. 35 It is difficult to interpret the discrepant data that have suggested both increases and decreases in peripheral BDNF in SLE patients and the association or not with NP manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, ours is the first report of PBMC production of neurotrophins in SLE. One other study assessed neurotrophin expression within B and T cells with flow cytometry, measuring the number of neurotrophin-producing cells, without quantifying the actual neurotrophin expression [24]. Our approach to PBMC assessment was also used in other disorders, such as multiple sclerosis [25, 19].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, NGF was shown to downregulate the monocytic inflammatory response via the trkA receptor [34]. On the other hand, neurotrophin overexpression in B cells of SLE patients was suggested as a hallmark of pathological activation [24]. Interestingly, it was shown that NGF might actually disrupt peripheral tolerance in psoriatic arthritis and rheumatoid arthritis, where it induced T cell proliferation and activation and decreased their sensitivity to TNF-α-induced apoptosis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, serum BDNF levels in SLE have been receiving increasing attention ( 54-59 ) and have been linked to various clinical parameters, suggesting the involvement of BDNF in the pathogenesis and progression of SLE. Fauchais et al ( 58 ) indicated that the serum levels of BDNF and the SLE disease activity index (SLEDAI) were not correlated. Although BDNF levels were reduced after treatment, they remained higher in patients with SLE than in healthy controls.…”
Section: Bdnf In Autoimmune Inflammatory Diseasesmentioning
confidence: 99%